Study the result of rabeprazole - levofloxacin - tinidazole regimen in patients with positive helicobacter pylory chronic gastritis - Anh, Hoang Thi Tu; Thang, Hoang Trong (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
None.